2014
DOI: 10.1021/cs500643r
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecylphosphate-Functionalized Iron Oxide Nanoparticles: Mild Oxidation of Benzyl C–H Bonds Exclusive to Carbonyls by Molecular Oxygen

Abstract: We report here a specially designed catalytic system consisting of hexadecylphosphate-functionalized iron oxide nanoparticles in oil/water biphasic emulsion. The iron oxide nanoparticles act as catalytic centers and the surfacebonded hexadecylphosphates as peripheral units which tune the activity of iron oxide and the access of reactants to the catalytic centers. The catalytic system is highly effective to oxidize the benzyl C−H bonds in a series of compounds to carbonyls exclusively by molecular oxygen under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Besides carboxylates, alkylphosphonic acids (and their deprotonated forms) are among the most common ligands for oxide and compound semiconductor nanomaterials due to strong coordination of the surfaces of these materials. 28 , 31 For example, the most common method to synthesize TDPA-capped CdSe QDs entails preparing a Cd phosphonate salt and mixing it with trioctylphosphine selenide (TOPSe) in a solvent consisting of trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO). 32 After NC growth, significant amounts of free phosphorus-containing molecules remain in the system; 31 P NMR is ideal to profile the components remaining in the sample solution after purification by different methods.…”
Section: Resultsmentioning
confidence: 99%
“…Besides carboxylates, alkylphosphonic acids (and their deprotonated forms) are among the most common ligands for oxide and compound semiconductor nanomaterials due to strong coordination of the surfaces of these materials. 28 , 31 For example, the most common method to synthesize TDPA-capped CdSe QDs entails preparing a Cd phosphonate salt and mixing it with trioctylphosphine selenide (TOPSe) in a solvent consisting of trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO). 32 After NC growth, significant amounts of free phosphorus-containing molecules remain in the system; 31 P NMR is ideal to profile the components remaining in the sample solution after purification by different methods.…”
Section: Resultsmentioning
confidence: 99%
“…This observation inspired us to optimize the pore structure of helical channels to develop highly selective artificial ion channels. Previous studies suggested that a queue of contiguous ion binding sites in the channel pore plays significant roles in highly selective conduction of channel models . Therefore, we wonder if a synthetic channel pore containing multiple ion binding sites can show the transporting specificity, as natural K + channels do.…”
Section: Figurementioning
confidence: 98%
“…In recent years, there has been published an impressive series of works devoted to the successful use of long‐chain n ‐alkylphosphonic acids in the nanoindustry for the design of diverse nanomaterials such as NPs, [25] nanocrystals, [26] nanotubes, [15c,27] nanolayers, nanofibers, nanorods, [28] tetrapods, [28a] nanoplatelets, [29] nanoflakes, [19b] which find application in optoelectronics, [29b,30] high‐tech technologies, [26b,27,31] catalysis, [25a] water treatment processes [25b] …”
Section: Introductionmentioning
confidence: 99%